Selection for early shoot vigour in wheat increases root hair length but reduces epidermal cell size of roots and leaves. (23rd February 2022) - Hendriks, Pieter-Willem; Ryan, Peter R; Hands, Philip; Rolland, Vivien; Gurusinghe, Saliya; Weston, Leslie A; Rebetzke, Greg J; Delhaize, Emmanuel
Abstract : The selection for early shoot vigour in wheat is associated with increased root hair length and changes to cell size in roots and shoots. Abstract: Six cycles of recurrent selection for early shoot vigour in wheat resulted in significant increases in leaf width and shoot biomass. Here, in replicated controlled-environment studies, the effect of early shoot vigour on root biomass, rhizosheath size, root hair length, and cell size in the roots and leaves was examined across different cycles of selection. Increased shoot vigour was associated with greater root biomass, larger rhizosheath size, and longer root hairs. Our findings demonstrate that rhizosheath size was a reliable surrogate for root hair length in this germplasm. Examination of the root epidermis revealed that the 'cell body' of the trichoblasts (hair-forming cells) and the atrichoblasts (non-hair-forming cells) decreased in size as shoot vigour increased. Therefore, in higher vigour germplasm, longer root hairs emerged from smaller trichoblasts so that total trichoblast volume (root hair plus cell body) was generally similar regardless of shoot vigour. Similarly, the sizes of the four main cell types on the leaf epidermis became progressively smaller as shoot vigour increased, which also increased stomatal density. The relationship between shoot vigour and root traits is considered, and the potential contribution of below-ground root traits to performance and competitiveness of high vigour germplasm is discussed.